KARAKTERISTIK INDIVIDU, GAYA KEPEMIMPINAN, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA DEPARTEMEN QUALITY LABORATORY PT. ALCON BATAM - Rayner Royzin Tnunay; Indra Firdiyansyah (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2022)
This study aims to determine the effect of leadership on the performance of elementary school teachers at Yehonala School, the effect of motivation on the performance of elementary school teachers at Yehonala School, the effect of work discipline on the performance of elementary school teachers at Yehonala School and the influence of leadership style, motivation and work discipline on the performance of elementary school teachers in the school Yehonala. The researcher uses the census method, which is to record the entire existing population. Based on the census in the field, the sample in this study was 34 elementary school teachers. Data collected by questionnaire technique. In the results of this study, the regression equation Y = (6.493) + 0.293X1 + 0.024X2 + 1.083X3 + e. The value of leadership style is obtained by t count 1.215 < 2.042 with a sig value of 0.234 >0.05 which indicates that leadership style has no effect and is significant on teacher performance, the value of motivation is obtained by t count 0.132 < 2.042 and sig value 0.896 > 0.05 which shows that leadership style has no effect and is significant on teacher performance, and the tcount value of work discipline is 4,080 > ttable 2,042, and sig 0.000 <0.05 which indicates that work discipline has an effect and is significant on teacher performance. The value of R2 is 0.718, which means that the variables of leadership style (X1), motivation (X2) and work discipline (X3) can explain the teacher’s performance variable by 71.8%, while 28.2% is explained by other variables not discussed in this study.